Imagining a different voice: A critical and caring approach to management education. Issue 4 (September 2019) - Heath, Teresa; O'Malley, Lisa; Tynan, Caroline
This article discusses the use of the moral philosophy known as the ethics of care to critically engage management students in ways that favour the development and enactment of a critical and responsible mentality towards business. We use this ethics to ground critical thinking in a moral framework in order to create a conversation in which new possibilities for sustainable and ethical practices might be discovered. Specifically, we identify four teaching practices that allow students to experience being both 'cared for' and 'one-caring' and explore how this creates a deeper and more critical moral engagement with those affected by businesses. We further propose a framework for applying a care-ethical approach for teaching and learning.